(untitled) (Journal of Bio-Science, 2023)
Lathyrus sativus known as grass pea belongs to the family of Fabaceae commonly grown for human consumption and livestock feed throughout the world. This study based on the morphological features of the basic chromosome numbers and numerical characterization of the karyotypes using total chromosome length (TCL), arm ratio and total fraction frequency. Outcome of BARI Khesari-2 is more effective than BARI Khesari-3 on the basis of mitotic index, nuclear volume and interphase chromosome volume. Whereas, mitotic index directly relevant to cell division; when MI high than cell division rate will be high. The two varieties (BARI Khesari-2 and BARI Khesari-3) were found to possess 2n = 14 chromosomes. Karyotype analysis is an essential tool for studying the genetic constitution of any organism. In this investigation, we found the karyotype formula of BARI Khesari-2 is 7L 4m + 2sm + 1st and BARI Khesari-3 is 7L 2m +3sm + 2st. Chromosome morphology showed a variation in the chromosome length, chromosome structure and centromere position of the accessions. Presence of sub-terminal chromosome in both varieties shows asymmetric karyotype which indicates advanceness. The variation in L. sativus may be regarded as having evolution and adaptive significance. J. Bio-Sci. 30(2): 59-65, 2022